(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The study on drug–protein interactions is an important field of interest because of the prospective of unraveling of drug action mechanisms and the possibility of designing novel medicines. Bovine serum albumin (BSA) has been studied extensively, because of its structural homology with human serum albumin (HSA). β-Sitosterol is a phytosterol compound which has a variety of pharmacological properties Luteolin 7- glucoside is a glycosyloxy flavones, which has a role as an antioxidant. In this study, the interaction between β-sitosterol and Luteolin – 7- glucoside with bovine serum albumin (BSA) was investigated at physiological pH 7.4 by fluorescence spectroscopy. The study revealed that the fluorescence quenching of BSA by molecules was a result of the formation of a molecule-BSA complex. Fluorescence quenching constants were determined using the Stern-Volmer to provide a measure of the binding affinity between the molecules and BSA. The results of thermodynamic parameters ΔG, ΔH, and ΔS at different temperatures indicated that action was an endothermic and spontaneous process, and hydrophobic interaction played a major role in molecule-BSA association.